ANALISIS DESKRIPTIF PADA FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT SISWA UNTUK MELANJUTKAN PENDIDIKAN KE TINGKAT PERGURUAN TINGGI - Ika Purnamasari; Memi Nor Hayati (Jurnal Statistika Universitas Muhammadiyah Semarang, 2018)
The success of human development in an area can be measured based on the level of education which is influenced by several factors, both internal and external. The mean years of schooling (MYS) are the basis for measuring the high level of education that affects the size of the Human Development Index (HDI). The aims of this study is to explore data based on internal and external factors that affect the interest of senior highschool students in the Penajam Paser Utara (PPU) to continue their education at college level. Exploration of data in this study was carried out using descriptive statistical analysis. Descriptive statistics are methods that are often used to process data and present it to be easier to understand, both in the form of diagrams and tables. Based on 292 respondents who are interested in continuing their study, it is known that the average levelof education of parents of respondents is still quite low. The level of education of parents affects the income level of parents, as many as 138 respondents have parents with an average income of one million to three million per month. Although the level of education and income of respondents parents is quite low, in fact, the ratio of respondents who areinterested in continuing their education to college institutions is 2.72 times greater than those of respondents who are not interested.  Keyword : descriptive statistics, HDI, MYS, PPU.